Physico-chemical and sensory characteristics of fresh cheeses fermented with Milk kefir and water kefir (Research, Society and Development, 2020)
The objective was to develop fresh cheeses with fermented milk kefir and water kefir to evaluate the physical-chemical and sensory properties, in addition to evaluating the physical properties of kefir grains and consumer profiles. Initially, four fresh cheese formulations were processed with a concentration of 1.0%, 2.0%, 3.0% and 4.0% fermented milk kefir and water kefir in a completely randomized design (DIC), for sensorially identify the best formulations. Subsequently, formulations with less concentration were processed in view of the fact that the assessors of the evaluation did not identify differences between the formulations. For the manufacture of cheese, two DIC treatments were constituted: 1) added with milk kefir; 2) added with water kefir, at a concentration of 1.0% fermented. The cheeses were evaluated for their physical-chemical composition: fat, protein, pH, acidity, color, moisture, ash and dry matter. Fresh cheeses were evaluated for physical-chemical properties, acceptance and purchase intention. The physical structure of milk kefir and water kefir demonstrated the presence of bacilli, which reinforces the probiotic nature of these products, however, research is needed to assess the presence of probiotic microorganisms to indicate their functional potential. Because the increase in the concentration of kefir fermented does not interfere sensorially in fresh cheeses, it is recommended to process fresh cheese formulations with kefir fermented in a lower concentration in order to reduce costs during cheese processing. The type of kefir fermented did not influence the nutritional parameters of fresh cheeses.